A developmental perspective on Library science - Lode Vijay Bhasker (AG Volumes, 2023)
All systems must be elevated to an increasingly user-friendly level as technology develops. The LMS will make life simpler for librarians. With the help of the LMS, librarians may deal with several problems at once. Users won’t have to wait in a huge line to return or check out books. All of the files are stored on only one computer. Librarians are responsible for evaluating the database and adding an appropriate entry. The library’s LMS system makes it possible to track down the requested volume. The LMS is built with fundamental capabilities, such as allowing the librarian to enter, browse, modify, and remove information about books and students. After gaining access, the hacker is free to change anything in the database.